Invasive fungal infection in Ramathibodi Hospital: A ten-year autopsy review - Noppadol Larbcharoensub (2018)
Objective: Determine the clinicopathological findings in autopsy cases with invasive fungal infection. Material and Method: The autopsy and medical records with invasive fungal infection in Ramathibodi Hospital between January 1997 and December 2006 were analyzed. The criterions for the diagnosis of invasive fungal infection were the evidence of fungal elements from histopathological section. The age, gender, underlying predisposing risk factors for the disease, clinical manifestations, extent of systemic organ involvement documented morphologically at autopsy, and fungal culture were analyzed. Results: There were 155 autopsy cases (73 male, 82 female; mean age 45.3 years, range 3 months to 87 years) with the diagnosis of invasive fungal infection. The common clinical presentations were fever (55.5%), and dyspnea (26.5%). The invasive fungal infection was associated with hematologic malignancy in 31%. The common mycoses were aspergillosis and candidiasis, which were observed in 88 and 80 cases, respectively. There were 32 cases (20.6%) of mixed fungal infection. Cultures from autopsy materials were positive for fungus in 80 cases out of 99 cases (80.8%). The most frequent site of fungal infection was in the lungs (74.8%), followed by gastrointestinal tract (28.4%), and brain (26.5%). Invasive fungal infection was diagnosed intravitally in 63.9% of total cases. Conclusion: A diagnosis of invasive fungal infection requires a high index of suspicion, especially in immunocompromised patients who presented with prolonged fever. Clinical specimens must be sent for histopathology and fungal culture for a definite diagnosis and an appropriate management. Therefore, the physician should inform the laboratory if invasive fungal infection is suspected because special media are necessary for the best recovery of fungi. In addition, the present study underscores the significance of autopsy as a diagnostic method and means of medical quality control.